Testing the Relationship Between the Real Estate Market Index and the Saudi Stock Market Index for the Period from 2015 AD - 2022 AD - Fallatah, Ammar Suliman; Khoj, Haitham Zaker; Akeel, Hatem Khaled (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to nowing the degree of correlation between the real estate market index, and the stock market index, and inflation in the Kingdom of Saudi Arabia during the years 2015-2022 AD, the study used the standard approach, which uses statistical analysis of time series to show the nature of the relationship between the real estate market index, the Saudi stock market index, and inflation, the limits test proved the absence of a relationship in the long term, and the results showed that the estimation of the relationship model in the short term did not achieve the effect of the real estate index and the inflation index on the stock index, while the effect of the inflation index on the real estate index was negatively affected, The results also showed that the stability of the two series of the real estate index and the stock index were not achieved, as the first differences were taken for them to become stable, and therefore they are integrated of degree (1), and the stability of the inflation rate index was also achieved, and therefore the degree of their integration is (zero), the results also showed the negative impact of the inflation rate on the real estate index.
Keywords: Real estate market index; stock market index; inflation